Low-water-absorption artificial stone unsaturated polyester resin and preparation method thereof
By using neopentyl hydroxypivalate and benzyl alcohol in artificial stone unsaturated polyester resin, the amount of the polyester is adjusted to control the hydrophobicity and thermal stability of the polyester chain, the problem of artificial stone products being prone to defects in high humidity environments is solved, and the effects of low water absorption, high dispersion and wear resistance are achieved.
Patent Information
- Application Number
- CN202510080273.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, artificial stone unsaturated polyester resin products are prone to holes, cracks and surface coating fall off in high humidity environments, affecting their aesthetics and comfort.
Neopentyl glycol hydroxypivalate and benzyl alcohol are used as main components. By adjusting their dosage in the formula, the hydrophobicity, thermal stability and flexibility of the polyester chain are controlled, thereby reducing water absorption, improving dispersion and mechanical properties.
Artificial stone unsaturated polyester resin with low water absorption, high dispersion, thermal stability and wear resistance is achieved, avoiding cracks and deformation problems of products in humid environments, while improving its aesthetics and service life.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of unsaturated polyester resins, and in particular relates to an artificial stone unsaturated polyester resin with low water absorption and a preparation method thereof. Background Art
[0002] Polyester can be obtained by dehydration and polycondensation of dicarboxylic acids and diols, and then unsaturated polyester resin can be obtained after dilution with a cross-linking agent. The cured products after unsaturated polyester resin is mixed with different fillers can be applied to many fields. For example, after unsaturated polyester resin is mixed with calcium carbonate powder, quartz powder, dolomite powder, and marble powder, it is toned by color paste pigments, and the double bonds in the polyester chain and styrene are cross-linked and cured under the action of accelerators and curing agents to obtain artificial marble products with excellent performance. This type of product is often used in wash basins, bathtubs, kitchen counters, craft sculptures, wall surfaces, and many other aspects. It is superior to its simple preparation process, lower cost than natural stone, and a wider range of appearance color choices. In today's society, consumers have a high degree of choice for it.
[0003] The common artificial stone unsaturated polyester resins on the market are usually synthesized by ethylene glycol, diethylene glycol, phthalic anhydride, isophthalic acid, terephthalic acid and maleic anhydride, and the end-capping is usually dicyclopentadiene or monobasic acid, such as benzoic acid. While pursuing low cost and product adaptation, there is a lack of improvement strategies for the defects that are very easy to appear in the products after the test of time. Because artificial stone unsaturated polyester resin products are mostly used in high humidity and water-immersed environments under human living conditions, over time, the products are very prone to dents, cracks, and surface coating shedding, affecting the appearance of the products and the comfort of users. This is largely related to the long-term immersion of the products in water and the water absorption rate. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a highly dispersed, highly thermally stable, wear-resistant, non-deformable, low-water-absorbent artificial stone unsaturated polyester resin and a preparation method thereof.
[0005] The technical solution adopted by the present invention to solve the technical problem is: an artificial stone unsaturated polyester resin, wherein the reaction raw materials include, by weight, 8-15 parts by weight of phthalic anhydride, 20-30 parts by weight of maleic anhydride, 22-38 parts by weight of hydroxypivalic acid neopentyl glycol ester, 4-12 parts by weight of propylene glycol, 6-12 parts by weight of ethylene glycol, 0.005-0.01 parts by weight of a polymerization inhibitor in the reaction stage, 0.005-0.015 parts by weight of an antioxidant in the reaction stage, 5-10 parts by weight of benzyl alcohol, 0.004-0.008 parts by weight of a polymerization inhibitor in the cooling stage, 0.015-0.025 parts by weight of paraffin, 40-45 parts by weight of a cross-linking agent, and 0.003-0.005 parts by weight of a polymerization inhibitor in the dilution stage.
[0006] Neopentyl glycol hydroxypivalate, abbreviated as HTPP, has a chemical name of 2,2-dimethyl-3-hydroxypropionic acid-2,2-dimethyl-3-carboxypropyl ester. It contains four methyl groups in its structure, which can increase the density of small branched methyl groups in the polyester chain, which is beneficial to increase the molecular weight of the polyester chain and increase the spatial structure of the polyester chain. In addition, the methyl group belongs to the hydrocarbon group, has uniform electron distribution, and is a non-polar group. It is not easy to form hydrogen bonds with polar water molecules, and exhibits a certain hydrophobicity in the polyester chain, which can effectively reduce the water absorption rate of unsaturated polyester resin.
[0007] At the same time, hydroxypivalate neopentyl glycol ester contains an ester bond and two saturated carbon atoms, both ends are hydroxyl groups and the carbon chain is relatively long, which effectively increases the hydroxyl density in the polyester, is beneficial to increase the polyester chain length and gives the unsaturated polyester resin a certain flexibility and thermal stability, effectively avoiding cracks and deformation in the product.
[0008] At present, the synthesis process of hydroxypivalate neopentyl glycol ester on the market is simple, the raw material consumption is low, the output is high and the quality is excellent, it is easy to obtain and the cost is low. Preferably, the mass proportion of hydroxypivalate neopentyl glycol ester in the unsaturated polyester resin is 18.5% to 27.5%.
[0009] Benzyl alcohol is an aromatic compound with a benzene ring in its structure. The benzene ring has a high electron cloud density and is hydrophobic. It has the characteristic of reducing water absorption in unsaturated polyester resins. At the same time, it increases the number of benzene rings in the polyester chain, effectively increases the steric hindrance of the molecular chain, and hinders water molecules from approaching the polyester chain to achieve the purpose of reducing water absorption. In addition, it can also improve the mechanical properties of unsaturated polyester resins, increase the rigidity of the molecular chain, and help optimize the hardness and wear resistance of the resin.
[0010] As a monoalcohol, benzyl alcohol has a certain end-capping effect. Unlike the commonly used monoacids for end-capping, the monoalcohol end-capping can be combined with free -COOH, effectively reducing the number of terminal carboxyl groups in the polyester chain and increasing the number of terminal hydroxyl groups. Compared with -OH, -COOH has higher reactivity. As a free end, it is easier to participate in more chemical reactions, such as esterification, acylation, etc., which is more detrimental to the thermal stability of the material. In addition, -COOH has higher hydrophilicity than -OH. Benzyl alcohol end-capping is better than monoacid end-capping in reducing water absorption. In addition, hydroxyl groups can effectively reduce surface tension. When artificial stone unsaturated polyester resin products need pigment paste to adjust the color, it can improve dispersion and reduce aggregation, which can effectively ensure that the color paste is more evenly dispersed and the products are more beautiful.
[0011] Preferably, the mass proportion of benzyl alcohol in the unsaturated polyester resin is 3.8% to 8.5%.
[0012] Since both hydroxypivalate and benzyl alcohol contain hydroxyl ends, they can be dehydrated and condensed with free carboxyl ends. When the amount of hydroxypivalate exceeds the upper limit, it will lead to large consumption of free carboxyl groups in the first step, affecting the utilization rate of benzyl alcohol end-capping in the second step; when the amount of hydroxypivalate is lower than the lower limit, the hydrophobic characteristics affected by its polymethyl branched structure are not significantly improved. When the amount of benzyl alcohol exceeds the upper limit, the proportion of monoalcohol in the formula is large, affecting the chain growth rate in the later stage; when the amount of benzyl alcohol is lower than the lower limit, the free carboxyl end-capping rate is low, the terminal hydroxyl density is low, the hydrophobic improvement is not obvious, and the effect of optimizing the dispersion of color paste pigments is not significant.
[0013] Therefore, by controlling the amount of neopentyl glycol hydroxypivalate and benzyl alcohol in the formula and limiting its scope of application, the obtained artificial stone unsaturated polyester resin can have the characteristics of low water absorption, high dispersion and thermal stability, excellent performance and not easy to deform to the maximum extent.
[0014] Preferably, in the above-mentioned low water-absorbent artificial stone unsaturated polyester resin, the antioxidant in the reaction stage is a mixture of trisnonylphenyl phosphite and triphenyl phosphite or one of them.
[0015] Preferably, in the above-mentioned low water-absorbent artificial stone unsaturated polyester resin, the inhibitor at each stage is one or more of hydroquinone, p-benzoquinone or 2-tert-butylhydroquinone.
[0016] Preferably, in the above-mentioned low water-absorbent artificial stone unsaturated polyester resin, the crosslinking agent is one or more of styrene, divinylbenzene or ethylene glycol dimethacrylate.
[0017] A method for preparing an unsaturated polyester resin for artificial stone with low water absorption, characterized in that it comprises the following steps: 1) Propylene glycol, ethylene glycol, neopentyl glycol hydroxypivalate, phthalic anhydride, maleic anhydride, polymerization inhibitor in the reaction stage, and antioxidant in the reaction stage are added into the reactor in the order of adding liquid materials first and then solid materials; 2) Under nitrogen protection, heat up to the outlet water temperature of 160-165°C, keep warm for 30 minutes, and control the distillation head temperature at 99-102°C; 3) After the outlet water is kept warm, heat it to 190℃ at 12-16℃ / h, and control the head temperature at 99-102℃. If the head temperature is >102℃, maintain the current temperature and reduce the nitrogen flow rate; if the head temperature is <102℃, increase the heating rate appropriately; if the head temperature is normal, heat it at 205-208℃ while heating it at 12-16℃; 4) The kettle temperature is controlled at 205-208℃ for heat preservation and polycondensation. According to the extension of heat preservation time and the decrease of distillation head temperature, the amount of nitrogen can be appropriately increased. The polycondensation is carried out for 30-60 minutes, and samples are taken to test the acid value. When the acid value reaches 50-60mgKOH / g, the temperature is lowered; 5) When the kettle temperature drops below 150°C, add benzyl alcohol, and then raise the kettle temperature to 205-208°C according to the heating rate of step 3) and keep it warm for polycondensation. 6) The kettle temperature is controlled at 205-208℃ for condensation polymerization for 2-3 hours until the acid value of the sample is <25mgKOH / g, then the temperature is lowered; 7) Cool down to below 190℃ and add the cooling stage inhibitor; 8) When the temperature continues to drop to 125°C, the inhibitor and cross-linking agent in the dilution stage are added to obtain an unsaturated polyester resin for artificial stone with low water absorption. The products thereof have the characteristics of low water absorption, high dispersion and thermal stability, excellent performance and not easy to deform.
[0018] Preferably, in the above method for preparing unsaturated polyester resin for artificial stone with low water absorption, the inner wall of the reaction kettle is provided with a spiral guide groove for enhancing the mixing effect of the materials.
[0019] Preferably, in the above method for preparing unsaturated polyester resin for artificial stone with low water absorption, a nitrogen inlet and a distillation head temperature sensor are arranged at the top of the reactor, and a nitrogen outlet and a cooling water inlet are arranged at the bottom.
[0020] Preferably, in the above-mentioned method for preparing unsaturated polyester resin for artificial stone with low water absorption, a stirring device is provided in the reactor, and the stirring device comprises a main stirring paddle and an auxiliary stirring paddle, the main stirring paddle is arranged at the center of the reactor, and the auxiliary stirring paddle is arranged near the inner wall of the reactor.
[0021] Compared with the prior art, the present invention has the following beneficial effects: the present invention firstly uses hydroxyl pivalate and benzyl alcohol as main components, and the hydrophobic structure of these two components effectively reduces the water absorption of resin, and improves the performance stability of products in humid environments. Secondly, the addition of benzyl alcohol improves the hydroxyl density, reduces the surface tension, makes the dispersion of pigment paste in resin higher, and ensures the aesthetics and color uniformity of products. In addition, the structural characteristics of hydroxyl pivalate and the end-capping effect of benzyl alcohol jointly improve the thermal stability and flexibility of resin, and effectively avoid the crack and deformation problems under high temperature conditions. At the same time, the addition of benzyl alcohol also improves the mechanical properties of resin, increases the rigidity of molecular chain, optimizes the hardness and wear resistance of resin, and makes products more durable. In terms of cost, the synthesis process of hydroxyl pivalate and benzyl alcohol is simple, the raw material consumption is low, the output is high and the quality is excellent, and it has high cost-effectiveness. Finally, through reasonable process optimization measures, such as reasonable feeding sequence, temperature control and stirring device setting, the reaction efficiency and product quality were further improved, ensuring the preparation of low water absorption artificial stone unsaturated polyester resin with excellent performance. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0023] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0024] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0026] Theoretical output = total feed amount - theoretical water output Theoretical water output = (moles of phthalic anhydride + moles of maleic anhydride) * 18 Among them, embodiment 7 is the best embodiment.
[0027] Example 1 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 10 parts by weight of phthalic anhydride, 25 parts by weight of maleic anhydride, 22 parts by weight of hydroxypivalic acid neopentyl glycol ester, 4 parts by weight of propylene glycol, 11 parts by weight of ethylene glycol, 7.5 parts by weight of benzyl alcohol, 45 parts by weight of styrene, 0.006 parts by weight of hydroquinone in the reaction stage, 0.007 parts by weight of trisnonylphenyl phosphite as an antioxidant in the reaction stage, 0.006 parts by weight of hydroquinone as an inhibitor in the cooling stage, 0.02 parts by weight of paraffin, 0.003 parts by weight of hydroquinone as an inhibitor in the dilution stage, hydroxypivalic acid neopentyl glycol ester accounts for 18.5% of the theoretical output, and benzyl alcohol accounts for 6.3% of the theoretical output.
[0028] Example 2 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 8 parts by weight of phthalic anhydride, 27.5 parts by weight of maleic anhydride, 25.5 parts by weight of neopentyl glycol hydroxypivalate, 4 parts by weight of propylene glycol, 12 parts by weight of ethylene glycol, 7.5 parts by weight of benzyl alcohol, 40 parts by weight of divinylbenzene, 0.01 parts by weight of p-benzoquinone as a polymerization inhibitor in the reaction stage, 0.009 parts by weight of triphenyl phosphite as an antioxidant in the reaction stage, 0.004 parts by weight of p-benzoquinone as a polymerization inhibitor in the cooling stage, 0.018 parts by weight of paraffin, 0.003 parts by weight of p-benzoquinone as a polymerization inhibitor in the dilution stage, neopentyl glycol hydroxypivalate accounts for 21.5% of the theoretical output, and benzyl alcohol accounts for 6.3% of the theoretical output.
[0029] Example 3 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 15 parts by weight of phthalic anhydride, 20 parts by weight of maleic anhydride, 30 parts by weight of hydroxypivalic acid neopentyl glycol ester, 5 parts by weight of propylene glycol, 8 parts by weight of ethylene glycol, 7.5 parts by weight of benzyl alcohol, 45 parts by weight of cross-linking agent styrene, 0.006 parts by weight of polymerization inhibitor hydroquinone in the reaction stage, 0.015 parts by weight of antioxidant trisnonylphenyl phosphite in the reaction stage, 0.007 parts by weight of polymerization inhibitor hydroquinone in the cooling stage, 0.022 parts by weight of paraffin, 0.004 parts by weight of polymerization inhibitor hydroquinone in the dilution stage, neopentyl glycol hydroxypivalate accounts for 24% of the theoretical output, and benzyl alcohol accounts for 6% of the theoretical output.
[0030] Example 4 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 14 parts by weight of phthalic anhydride, 26 parts by weight of maleic anhydride, 34 parts by weight of neopentyl glycol hydroxypivalate, 8 parts by weight of propylene glycol, 8 parts by weight of ethylene glycol, 7.5 parts by weight of benzyl alcohol, 45 parts by weight of cross-linking agent styrene, 0.005 parts by weight of hydroquinone as a polymerization inhibitor in the reaction stage, 0.011 parts by weight of triphenyl phosphite as an antioxidant in the reaction stage, 0.006 parts by weight of hydroquinone as a polymerization inhibitor in the cooling stage, 0.015 parts by weight of paraffin, 0.005 parts by weight of hydroquinone as a polymerization inhibitor in the dilution stage, neopentyl glycol hydroxypivalate accounts for 25% of the theoretical output, and benzyl alcohol accounts for 5.5% of the theoretical output.
[0031] Example 5 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 11 parts by weight of phthalic anhydride, 28 parts by weight of maleic anhydride, 38 parts by weight of neopentyl glycol hydroxypivalate, 7 parts by weight of propylene glycol, 8 parts by weight of ethylene glycol, 7.5 parts by weight of benzyl alcohol, 45 parts by weight of cross-linking agent styrene, 0.006 parts by weight of hydroquinone as a polymerization inhibitor in the reaction stage, 0.007 parts by weight of triphenyl phosphite as an antioxidant in the reaction stage, 0.005 parts by weight of hydroquinone as a polymerization inhibitor in the cooling stage, 0.019 parts by weight of paraffin, 0.002 parts by weight of hydroquinone as a polymerization inhibitor in the dilution stage, neopentyl glycol hydroxypivalate accounts for 27.5% of the theoretical output, and benzyl alcohol accounts for 5.4% of the theoretical output.
[0032] The method for preparing the low water-absorbent unsaturated polyester resin described in Examples 1-5 comprises the following steps: 1) Propylene glycol, ethylene glycol, neopentyl glycol hydroxypivalate, phthalic anhydride, maleic anhydride, polymerization inhibitor in the reaction stage, and antioxidant in the reaction stage are added into the reactor in the order of adding liquid materials first and then solid materials; 2) Under nitrogen protection, heat up to the outlet water temperature of 160°C, keep warm for 30 minutes, and control the distillation head temperature at 99°C~102°C; 3) After the outlet water is kept warm, heat it to 190℃ at a rate of 12℃ / h, and control the head temperature at 99℃~102℃. If the head temperature is >102℃, maintain the current temperature and reduce the nitrogen flow rate; if the head temperature is <102℃, increase the heating rate appropriately; if the head temperature is normal, heat it to 205℃ at a rate of 12℃ / h and keep warm; 4) The kettle temperature is controlled at 205℃ for heat preservation and polycondensation. The amount of nitrogen can be appropriately increased according to the extension of the heat preservation time and the decrease of the distillation head temperature. The polycondensation is carried out for 30 minutes, and the acid value is tested by sampling. When the acid value reaches 50mgKOH / g, the temperature is lowered; 5) When the kettle temperature drops below 150°C, add benzyl alcohol, and then raise the kettle temperature to 205°C at the heating rate in step 3) and keep it warm for polycondensation. 6) The kettle temperature is controlled at 205℃ for condensation for 2 hours until the acid value is <25mgKOH / g, then the temperature is lowered; 7) Cool down to below 190℃ and add the cooling stage inhibitor; 8) When the temperature continues to drop to 125°C, add the dilution stage inhibitor and cross-linking agent to obtain the artificial stone unsaturated polyester resin with low water absorption.
[0033] Example 6 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 15 parts by weight of phthalic anhydride, 30 parts by weight of maleic anhydride, 30 parts by weight of hydroxypivalic acid neopentyl glycol ester, 12 parts by weight of propylene glycol, 8 parts by weight of ethylene glycol, 5 parts by weight of benzyl alcohol, 40 parts by weight of cross-linking agent styrene, 0.01 parts by weight of hydroquinone as a polymerization inhibitor in the reaction stage, 0.005 parts by weight of triphenyl phosphite as an antioxidant in the reaction stage, 0.007 parts by weight of hydroquinone as a polymerization inhibitor in the cooling stage, 0.025 parts by weight of paraffin, 0.004 parts by weight of hydroquinone as a polymerization inhibitor in the dilution stage, neopentyl glycol hydroxypivalate accounts for 22.6% of the theoretical output, and benzyl alcohol accounts for 3.8% of the theoretical output.
[0034] Example 7 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 15 parts by weight of phthalic anhydride, 26 parts by weight of maleic anhydride, 30 parts by weight of hydroxypivalic acid neopentyl glycol ester, 10 parts by weight of propylene glycol, 8 parts by weight of ethylene glycol, 6 parts by weight of benzyl alcohol, 45 parts by weight of cross-linking agent styrene, 0.01 parts by weight of hydroquinone as a polymerization inhibitor in the reaction stage, 0.008 parts by weight of trisnonylphenyl phosphite as an antioxidant in the reaction stage, 0.005 parts by weight of hydroquinone as a polymerization inhibitor in the cooling stage, 0.024 parts by weight of paraffin, 0.003 parts by weight of hydroquinone as a polymerization inhibitor in the dilution stage, neopentyl glycol hydroxypivalate accounts for 22.5% of the theoretical output, and benzyl alcohol accounts for 4.5% of the theoretical output.
[0035] Example 8 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 11 parts by weight of phthalic anhydride, 25 parts by weight of maleic anhydride, 30 parts by weight of hydroxypivalic acid neopentyl glycol ester, 12 parts by weight of propylene glycol, 6 parts by weight of ethylene glycol, 7.5 parts by weight of benzyl alcohol, 40 parts by weight of cross-linking agent styrene, 0.008 parts by weight of 2-tert-butylhydroquinone as a polymerization inhibitor in the reaction stage, 0.014 parts by weight of trisnonylphenyl phosphite as an antioxidant in the reaction stage, 0.004 parts by weight of 2-tert-butylhydroquinone as a polymerization inhibitor in the cooling stage, 0.023 parts by weight of paraffin, 0.002 parts by weight of 2-tert-butylhydroquinone as a polymerization inhibitor in the dilution stage, hydroxypivalic acid neopentyl glycol ester accounts for 23.9% of the theoretical output, and benzyl alcohol accounts for 6% of the theoretical output.
[0036] Example 9 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 10 parts by weight of phthalic anhydride, 21 parts by weight of maleic anhydride, 28 parts by weight of hydroxypivalic acid neopentyl glycol ester, 5 parts by weight of propylene glycol, 7 parts by weight of ethylene glycol, 9 parts by weight of benzyl alcohol, 45 parts by weight of a cross-linking agent, 0.009 parts by weight of hydroquinone as a polymerization inhibitor in the reaction stage, 0.015 parts by weight of trisnonylphenyl phosphite as an antioxidant in the reaction stage, 0.007 parts by weight of hydroquinone as a polymerization inhibitor in the cooling stage, 0.02 parts by weight of paraffin, 0.004 parts by weight of hydroquinone as a polymerization inhibitor in the dilution stage, neopentyl glycol hydroxypivalate accounts for 23.3% of the theoretical output, and benzyl alcohol accounts for 7.5% of the theoretical output.
[0037] Example 10 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 11 parts by weight of phthalic anhydride, 22 parts by weight of maleic anhydride, 28 parts by weight of hydroxypivalic acid neopentyl glycol ester, 6 parts by weight of propylene glycol, 6 parts by weight of ethylene glycol, 10 parts by weight of benzyl alcohol, 40 parts by weight of cross-linking agent styrene, 0.005 parts by weight of hydroquinone as a polymerization inhibitor in the reaction stage, 0.005 parts by weight of trisnonylphenyl phosphite as an antioxidant in the reaction stage, 0.008 parts by weight of hydroquinone as a polymerization inhibitor in the cooling stage, 0.021 parts by weight of paraffin, 0.003 parts by weight of hydroquinone as a polymerization inhibitor in the dilution stage, neopentyl glycol hydroxypivalate accounts for 23.8% of the theoretical output, and benzyl alcohol accounts for 8.5% of the theoretical output.
[0038] The method for preparing the low water-absorbent unsaturated polyester resin described in Examples 6-10 comprises the following steps: 1) Propylene glycol, ethylene glycol, neopentyl glycol hydroxypivalate, phthalic anhydride, maleic anhydride, polymerization inhibitor in the reaction stage, and antioxidant in the reaction stage are added into the reactor in the order of adding liquid materials first and then solid materials; 2) Under nitrogen protection, heat up to the outlet water temperature of 165°C, keep warm for 30 minutes, and control the distillation head temperature at 99°C~102°C; 3) After the outlet water is kept warm, heat it to 190℃ at a rate of 16℃ / h, and control the head temperature at 99℃~102℃. If the head temperature is >102℃, maintain the current temperature and reduce the nitrogen flow rate; if the head temperature is <102℃, increase the heating rate appropriately; if the head temperature is normal, heat it to 208℃ at a rate of 16℃ / h and keep warm; 4) The kettle temperature is controlled at 208℃ for heat preservation and polycondensation. The amount of nitrogen can be appropriately increased according to the extension of the heat preservation time and the decrease of the distillation head temperature. The polycondensation is carried out for 60 minutes, and samples are taken to test the acid value. When the acid value reaches 60mgKOH / g, the temperature is lowered; 5) When the kettle temperature drops below 150°C, add benzyl alcohol, and then raise the kettle temperature to 208°C according to the heating rate of step 3) and keep it warm for polycondensation. 6) The kettle temperature is controlled at 208℃ for 3 hours of polycondensation until the acid value is <25mgKOH / g, then the temperature is lowered; 7) Cool down to below 190℃ and add the cooling stage inhibitor; 8) When the temperature continues to drop to 125°C, add the dilution stage inhibitor and cross-linking agent to obtain the artificial stone unsaturated polyester resin with low water absorption.
[0039] Comparative Example 1 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 25 parts by weight of phthalic anhydride, 25 parts by weight of maleic anhydride, 0 parts by weight of neopentyl glycol hydroxypivalate, 18.5 parts by weight of propylene glycol, 17 parts by weight of ethylene glycol, 0 parts by weight of benzyl alcohol, 40 parts by weight of cross-linking agent styrene, 0.006 parts by weight of polymerization inhibitor in the reaction stage, 0.007 parts by weight of trisnonylphenyl phosphite as an antioxidant in the reaction stage, 0.006 parts by weight of polymerization inhibitor in the cooling stage, 0.02 parts by weight of paraffin, 0.003 parts by weight of polymerization inhibitor in the dilution stage, neopentyl glycol hydroxypivalate accounts for 0% of the theoretical output, and benzyl alcohol accounts for 0% of the theoretical output.
[0040] Comparative Example 2 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 8 parts by weight of phthalic anhydride, 25 parts by weight of maleic anhydride, 30 parts by weight of hydroxypivalic acid neopentyl glycol ester, 18 parts by weight of propylene glycol, 14 parts by weight of ethylene glycol, 0 parts by weight of benzyl alcohol, 45 parts by weight of cross-linking agent styrene, 0.006 parts by weight of polymerization inhibitor in the reaction stage, 0.007 parts by weight of trisnonylphenyl phosphite as an antioxidant in the reaction stage, 0.006 parts by weight of polymerization inhibitor in the cooling stage, 0.02 parts by weight of paraffin, 0.003 parts by weight of polymerization inhibitor in the dilution stage, hydroxypivalic acid neopentyl glycol ester accounts for 22.3% of the theoretical output, and benzyl alcohol accounts for 0% of the theoretical output.
[0041] Comparative Example 3 The low water-absorbent artificial stone unsaturated polyester resin described in this embodiment includes the following raw materials in parts by weight: 25 parts by weight of phthalic anhydride, 25 parts by weight of maleic anhydride, 0 parts by weight of hydroxypivalic acid neopentyl glycol ester, 18 parts by weight of propylene glycol, 15 parts by weight of ethylene glycol, 7.5 parts by weight of benzyl alcohol, 45 parts by weight of cross-linking agent styrene, 0.006 parts by weight of polymerization inhibitor in the reaction stage, 0.007 parts by weight of trisnonylphenyl phosphite as an antioxidant in the reaction stage, 0.006 parts by weight of polymerization inhibitor in the cooling stage, 0.02 parts by weight of paraffin, 0.003 parts by weight of polymerization inhibitor in the dilution stage, hydroxypivalic acid neopentyl glycol ester accounts for 0% of the theoretical output, and benzyl alcohol accounts for 5.9% of the theoretical output.
[0042] Performance Test: The artificial stone unsaturated polyester resin obtained in the examples and comparative examples was used to prepare casting product samples, and the performance of the samples was tested. The test standards are as follows: Tensile strength test standard GB / T 2567-2008; unit: MPa.
[0043] Tensile elastic modulus test standard GB / T 2567-2008; unit: MPa.
[0044] Elongation at break test standard GB / T 2567-2008; unit: %.
[0045] Bending strength test standard GB / T 2567-2008; unit: MPa.
[0046] Flexural elastic modulus test standard GB / T 2567-2008; unit: MPa.
[0047] Impact strength test standard GB / T 2567-2008; unit Kj / m 2 .
[0048] Barcol hardness test standard GB / T 3854-2005; unit: Hba.
[0049] Heat deformation temperature test standard GB / T 2567-2008; unit: ℃.
[0050] Water absorption test standard GB / T1034-2008; unit: %.
[0051] The performance test results of Examples 1 to 5 are shown in Table 1 below.
[0052] Table 1 .
[0053] The performance test results of Examples 6 to 10 are shown in Table 2 below.
[0054] Table 2 .
[0055] The performance test results of Comparative Examples 1 to 3 are shown in Table 3 below.
[0056] Table 3 .
[0057] The water absorption rates of Examples 1 to 10 and Comparative Examples 1 to 3 are shown in Table 4 below.
[0058] Table 4 .
[0059] According to the data of Table 1, Table 2 and Table 4, the artificial stone unsaturated polyester resin obtained by Examples 1 to 10 has good mechanical properties, tensile strength can reach more than 85MPa, bending strength can reach more than 120MPa, hardness can reach more than 35Hba, and water absorption rate is less than 0.2%. The formula of Comparative Example 1 does not contain hydroxypivalic acid neopentyl glycol ester and benzyl alcohol; Comparative Example 2 contains hydroxypivalic acid neopentyl glycol ester and accounts for 16.3%, which is within the preferred range and does not contain benzyl alcohol; Comparative Example 3 contains benzyl alcohol and accounts for 11.5%, which is within the preferred range and does not contain hydroxypivalic acid neopentyl glycol ester. According to the data of Table 3 and Table 4, when the formula does not contain hydroxypivalic acid neopentyl glycol ester and benzyl alcohol or when both are used alone, the mechanical properties are low, the tensile strength is less than 75MPa, the bending strength is less than 90MPa, the hardness is less than 25Hba, and the water absorption rate is more than 0.3%.
[0060] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A low water-absorbent artificial stone unsaturated polyester resin, characterized in that: The reaction raw materials include 8-15 parts by weight of phthalic anhydride, 20-30 parts by weight of maleic anhydride, 22-38 parts by weight of hydroxypivalic acid neopentyl glycol ester, 4-12 parts by weight of propylene glycol, 6-12 parts by weight of ethylene glycol, 0.005-0.01 parts by weight of a polymerization inhibitor in the reaction stage, 0.005-0.015 parts by weight of an antioxidant in the reaction stage, 5-10 parts by weight of benzyl alcohol, 0.004-0.008 parts by weight of a polymerization inhibitor in the cooling stage, 0.015-0.025 parts by weight of paraffin, 40-45 parts by weight of a cross-linking agent, and 0.003-0.005 parts by weight of a polymerization inhibitor in the dilution stage.
2. The low water-absorbent artificial stone unsaturated polyester resin according to claim 1, characterized in that: The mass proportion of hydroxypivalate neopentyl glycol ester in the unsaturated polyester resin is 18.5% to 27.5%.
3. The low water-absorbent artificial stone unsaturated polyester resin according to claim 1, characterized in that: The mass proportion of benzyl alcohol in the unsaturated polyester resin is 3.8% to 8.5%.
4. The low water-absorbent artificial stone unsaturated polyester resin according to claim 1, characterized in that: The antioxidant in the reaction stage is a mixture of trisnonylphenyl phosphite and triphenyl phosphite or one of them.
5. The low water-absorbent artificial stone unsaturated polyester resin according to claim 1, characterized in that: The inhibitor in each stage is one or more of hydroquinone, p-benzoquinone or 2-tert-butylhydroquinone.
6. The low water-absorbent artificial stone unsaturated polyester resin according to claim 1, characterized in that: The crosslinking agent is one or more of styrene, divinylbenzene or ethylene glycol dimethacrylate.
7. A method for preparing the low water-absorbent artificial stone unsaturated polyester resin according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Propylene glycol, ethylene glycol, neopentyl glycol hydroxypivalate, phthalic anhydride, maleic anhydride, polymerization inhibitor in the reaction stage, and antioxidant in the reaction stage are added into the reactor in the order of adding liquid materials first and then solid materials; 2) Under nitrogen protection, heat up to the outlet water temperature of 160℃~165℃, keep warm for 30 minutes, and control the distillation head temperature at 99℃~102℃; 3) After the outlet water is kept warm, heat it to 190℃ at a rate of 12℃ / h~16℃ / h, and control the head temperature at 99℃~102℃; if the head temperature is >102℃, maintain the current temperature and reduce the nitrogen flow; if the head temperature is <102℃, increase the heating rate; if the head temperature is normal, heat it to 205℃~208℃ at a rate of 12℃ / h~16℃ / h and keep warm; 4) The kettle temperature is controlled at 205℃~208℃ for condensation polymerization for 30min~60min, and samples are taken to test the acid value. When the acid value reaches 50mgKOH / g~60mgKOH / g, the temperature is lowered; 5) When the kettle temperature drops below 150°C, add benzyl alcohol, and then raise the kettle temperature to 205°C~208°C according to the heating rate of step 3) and keep it warm for polycondensation; 6) The kettle temperature is controlled at 205℃~208℃ for condensation polymerization for 2h~3h, and then the temperature is lowered when the acid value is <25mgKOH / g after sampling; 7) Cool down to below 190℃ and add the cooling stage inhibitor; 8) Continue to cool down to 125°C, add the inhibitor and cross-linking agent from the dilution stage to obtain the product.
8. The method for preparing an unsaturated polyester resin for artificial stone with low water absorption according to claim 7, characterized in that: The inner wall of the reactor is provided with a spiral guide groove to enhance the mixing effect of the materials.
9. The method for preparing an unsaturated polyester resin for artificial stone with low water absorption according to claim 7, characterized in that: The top of the reactor is provided with a nitrogen inlet and a distillation head temperature sensor, and the bottom is provided with a nitrogen outlet and a cooling water inlet.
10. The method for preparing an unsaturated polyester resin for artificial stone with low water absorption according to claim 7, characterized in that: The reactor is provided with a stirring device, which comprises a main stirring paddle and an auxiliary stirring paddle. The main stirring paddle is arranged at the center of the reactor, and the auxiliary stirring paddle is arranged near the inner wall of the reactor.
Citation Information
Patent Citations
Hydrolysis-resistant unsaturated polyester resin and preparation method thereof
CN101792511A
Antibacterial and anti-mildew aqueous shell powder and nano-silver coating and production device thereof
CN107722698A
Epoxy acrylic fluorine-containing resin modified saturated polyester resin and preparation method thereof
CN111363130A
High molecular unsaturated polyester resin and its production
JP1998251388A
Method for producing radical curing powder coating material
JP2007231160A